Analysis of HOTS Instrument for Prospective Physics Teacher Using Generalized Partial Credit Model - Duden Saepuzaman; Edi Istiyono; H Haryanto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This study aims to analyze item parameters' characteristics and estimate prospective physics teachers' ability on the Higher Order Thinking Skills (HOTS) Instrument using the Generalized Partial Credit Model (GPCM). The research subjects were 251 prospective physics teacher students in two universities concerned with producing prospective teacher graduates. Two-Tier Multiple Choice (TTMC) forms with a polytomous score of four categories make up the test instrument. Data analysis includes two stages: testing assumptions and the suitability of the Politomus IRT model. The results showed that the most suitable polytomous scoring IRT model was GPCM2PL. The item parameter analysis for the HOTS Instrument test shows the discriminating power parameter (a) value for all items included in the good category, namely the interval 0.00 to 2.00. The difficulty level analysis (b) also shows the percentage of 100% of items included in the medium category because the b value of all items is in the interval (-2) to (2).